The search for meaning and engagement among Malaysian academics - Goh, Victor Weng Yew (2019)
This thesis studies the work experience of Malaysian academics through the theoretical framework of the Job Characteristics Model (JCM). Specifically, this research aimed to explore what constitutes work for Malaysian academics, and to examine the variables that lead towards workplace meaningfulness and work engagement. This was accomplished through three studies. The first qualitative study was carried out on 15 full-time academic respondents recruited from a range of higher education institutions (HEIs) in Malaysia, and aimed to examine what are the job characteristics that make up their work experience as Malaysian academics, including the challenges and motivations they face in the workplace and their reported attitudes and beliefs towards their work. The findings were also analysed through the lens of the JCM to determine if the characteristics present in the workplace are relatable to the job characteristics postulated by the JCM. Results indicated that some of the job characteristics that make up the Malaysian academic work experience are related to the characteristics of the JCM, in addition to several other factors such as organisational support, authorship, task variety, meaningful work, and elevated levels of burnout. The second quantitative study analysed the relationship between the reported factors in the first study with job psychological meaningfulness and also sought to generalize the findings of the first study to the general population of Malaysian academics. 350 participants were recruited from a range of Malaysian HEIs. Results indicated significant relationships between the JCM factors of Autonomy, Skill Variety, Task Significance, and Task Identity with job psychological meaningfulness, while Feedback was not a significant predictor. Additionally, factors such as Task Variety and Authorship was also a significant predictor of job psychological meaningfulness. Results also indicated a high level of burnout among Malaysian academics in general, indicating a generalisability of the results from the first study to the Malaysian academic population. The third study examined the relationship between the JCM factors, the psychological state of job meaningfulness, and work engagement levels among the same participants in Study 2. The relationship between burnout and work engagement was also studied. Results showed significant relationships between job psychological meaningfulness and work engagement, as well as significant mediated relationships between the JCM factors and work engagement with job psychological meaningfulness as a mediator. Burnout was also found to be significantly predictive of work engagement, as well as a significant mediator of the relationship between job psychological meaningfulness and work engagement. Implications of these results for the Malaysian higher education sector are discussed.